A heuristic approach for solving a rich min-max vehicle routing problem with mixed fleet and mixed demand. (July 2017) - Yakıcı, Ertan
Highlights: We give a model of a rich vehicle routing problem with mixed fleet and mixed demand. We propose a heuristic approach for this new variant of vehicle routing problem. The solution approach gives good results in numerical experiments. Abstract: We propose a new heuristic approach for a new variant of vehicle routing problem with a min-max objective function and mixed types of service demands satisfied by a mixed fleet. It is assumed that vehicles with unlimited service capacity, which have different service and transfer speeds, operate on demand points grouped in regions with boundaries that cannot be passed. The proposed solution method is based on swarm intelligence. A numerical study is carried out to evaluate the performance of the proposed method.